Cozy or Tense? Rethinking Employee Voice Within Enterprise Unionism in Japan - Ryohei Nakagawa (AAOS Transactions)
This study examines why labor unions in Japan typically preserve their negotiation powers within the enterprise unionism framework, despite criticism of potentially fostering collusive labor-management relations and weak external oversight. By conducting a qualitative analysis from extensive interview data, this research investigates the modifications in the unions’ two types of voices throughout the reform period around 2000, when employees were exposed to the increased risk of being put at a disadvantage during business downturns. This study aimed to elucidate the strategies employed by labor unions to effectively utilize both engagement voice （EV） and negotiation voice （NV） inextricably, thereby offering an explanation for the persistence of enterprise unionism without compromising the adequate tension of labor-management relations. It provided a novel theoretical contribution by examining the strengths and limitations of enterprise-based unions’ voice behaviors in Japan.